PENDIDIKAN KARAKTER DISIPLIN BERBASIS PESANTREN - Mujib santoso, Mujib santoso; Syaiful Hadi (As-Sulthan Journal of Education, 2025)
Character education in discipline is an important aspect in shaping responsible, honest, and integrity-driven individuals. Islamic boarding schools (pesantren), as traditional educational institutions, play a strategic role in instilling discipline values through a holistic approach that encompasses spiritual, social, and academic aspects. This study aims to comprehensively examine the concept of discipline-based character education in pesantren, the methods employed, and its impact on the character development of students (santri). The research was conducted using a descriptive qualitative approach through a case study at one pesantren. Data were collected through interviews and observations. The findings indicate that the implementation of discipline-based character education in pesantren is highly effective due to a conducive environment, the habituation of Islamic values, and strict supervision from the kyai (religious leaders) and ustadz (teachers). Santri are taught not only discipline in worship but also in daily life, including aspects of time management, social ethics, and adherence to rules. In conclusion, discipline-based character education in pesantren can serve as an effective educational model for shaping a strong character in the younger generation, enabling them to face the challenges of the times.